2011
DOI: 10.1111/j.1528-1167.2011.03068.x
|View full text |Cite
|
Sign up to set email alerts
|

Jeavons syndrome existing as occipital cortex initiating generalized epilepsy

Abstract: Summary Purpose:  Jeavons syndrome (JS) is one of the underreported epileptic syndromes characterized by eyelid myoclonia (EM), eye closure–induced seizures/electroencephalography (EEG) paroxysms, and photosensitivity. JS has been proposed as idiopathic generalized epilepsy (IGE) because of normal posterior dominant background activity and paroxysmal generalized ictal epileptiform discharges (EDs). However, we noticed subtle occipital EDs preceding EM and interictal posterior EDs using digital video‐EEG. We st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
58
1
5

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(70 citation statements)
references
References 14 publications
6
58
1
5
Order By: Relevance
“…Sharp alpha rhythms and isolated occipital spikes can be seen in EMA [35]. As shown in recent studies, the occipital cortex plays a role in pathophysiology of some epilepsies in which ECLS, fixation-off sensitivity (FOS), and photosensitivity are the initiating factors [36][37][38]. However, interestingly, we also saw frontal focal abnormalities in 4 patients with pure EMA (Fig.…”
Section: Discussionmentioning
confidence: 58%
“…Sharp alpha rhythms and isolated occipital spikes can be seen in EMA [35]. As shown in recent studies, the occipital cortex plays a role in pathophysiology of some epilepsies in which ECLS, fixation-off sensitivity (FOS), and photosensitivity are the initiating factors [36][37][38]. However, interestingly, we also saw frontal focal abnormalities in 4 patients with pure EMA (Fig.…”
Section: Discussionmentioning
confidence: 58%
“…Although focal EEG abnormalities in posterior regions have recently been reported [9], their possible clinical counterpart, namely visual aura, was not reported in association with the EMA syndrome, which is a unique syndrome. We found that EMA is common among the IGE patients having visual aura.…”
Section: Discussionmentioning
confidence: 95%
“…In the vast majority of cases, ECS is only seen with lights on, and it has, therefore, been suggested that the response is generated in the visual cortex, supported by the EEG [14]. However, the eyelid myocloni of ECS are not invariably accompanied by SW discharges [15].…”
Section: Descriptionmentioning
confidence: 98%